(untitled) (Revista Geografias, 2017)
The aim of this paper is using TerraME framework to develop a model that contributes in understanding the spatiotemporal behaviour of dengue transmission and the strength of control strategies. During the implementation of our model, it was necessary to adopt rules and input parameters, which represent potential determinants factors for dynamic transmission of dengue fever. The use of these rules allows simulating scenarios of epidemics in the absence and in the presence of dengue transmission control measures.